2008
DOI: 10.1051/medsci/2008242185
|View full text |Cite
|
Sign up to set email alerts
|

lschémie cérébrale

Abstract: L'ischémie cérébrale est la résultante d'une insuffisance ou d'un arrêt d'apport sanguin cérébral entraînant une suppression des apports en glucose et en oxygène. Elle peut être provoquée par un accident vasculaire céré-bral (thrombose, compression ou rupture artérielle) et affecter ainsi un territoire délimité (ischémie focale) ou bien toucher tout le cerveau dans le cas d'un arrêt cardiaque temporaire (ischémie globale). La durée de l'ischémie et l'étendue des zones détériorées détermi-nent la gravité des ré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In support of this possibility, both Trio and Tiam1 are expressed in the hippocampus CA1 (Ehler et al, 1997; Ma et al, 2005), and interestingly Tiam1 has been shown to mediate NMDA receptor activation of Rac1 in neurons (Tolias et al, 2005). This is intriguing as activation of NMDA receptors by excess glutamate is a proposed early step in the signaling cascade underlying cerebral ischemia-induced neuronal damage and cell death (Benquet et al, 2008). Interestingly, glutamate has been shown to induce activation of Rac1 in human neuroblastoma cells, an effect correlated with glutamate-induced neuronal cell death (Nikolova et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this possibility, both Trio and Tiam1 are expressed in the hippocampus CA1 (Ehler et al, 1997; Ma et al, 2005), and interestingly Tiam1 has been shown to mediate NMDA receptor activation of Rac1 in neurons (Tolias et al, 2005). This is intriguing as activation of NMDA receptors by excess glutamate is a proposed early step in the signaling cascade underlying cerebral ischemia-induced neuronal damage and cell death (Benquet et al, 2008). Interestingly, glutamate has been shown to induce activation of Rac1 in human neuroblastoma cells, an effect correlated with glutamate-induced neuronal cell death (Nikolova et al, 2005).…”
Section: Discussionmentioning
confidence: 99%